Bubble Up Induced Graphene Microspheres for Engineering Capacitive Energy Storage (Adv. Energy Mater. 16/2023). Issue 16 (26th April 2023) - Li, Xiangming; Zheng, Qinwen; Li, Congming; Liu, Gangqiang; Yang, Qingzhen; Wang, Yingche; Sun, Pengcheng; Tian, Hongmiao; Wang, Chunhui; Chen, Xiaoliang; Shao, Jinyou
Abstract : Supercapacitors Translating the materials metrics of graphene into supercapacitor performance is critical but engineering capacitive energy storage is challenging. In article number 2203761, Jinyou Shao and co‐workers introduce a bubble‐induced method for fabricating graphene microspheres with high ion conductivity and efficient utilization of surface area, enabling stack supercapacitors to deliver a high energy density of 83.4 Wh L −1, close to that of lead‐acid batteries.